Simulation of the Asphaltene Deposition Rate in Oil Wells under Different Multiphase Flow Condition - Wang, Xiaoming; Dong, Pingchuan; Zhang, Youheng; Gao, Xiaodong; Chen, Shun; Tian, Ming; Cui, Yongxing (Energies (Basel), 2024)
As the wellbore pressure falls below the bubble point pressure, the light components in the oil phase are liberated, forming additional vapor, and the single-phase flow becomes a gas–liquid two-phase flow. However, most studies simplify the multiphase flow to a single-phase flow to study asphaltene deposition in wellbores. This assumption under multiphase conditions may lead to inaccurate prediction results and a substantial economic and operational burden for the oil and gas industry. Therefore, it is crucial to predict the deposition rate of asphaltene in a multiphase flow to assist in minimizing this issue. To do so, the volume of fluid coupling level-set (VOSET) model was used to obtain the flow pattern (bubble, slug, churn, and annular) in the current work. In the next step, the VOSET + k-ε turbulent + DPM models were used to simulate asphaltene deposition in a multiphase flow. Finally, the effects of different parameters, such as the gas superficial velocity, liquid superficial velocity, particle diameter, interfacial tension, viscosity, and average deposition rate, were investigated. The findings revealed that the maximum average deposition rate of asphaltene particles in a bubble flow is 1.35, 1.62, and 2 times that of a slug flow, churning flow, and annular mist flow, respectively. As the apparent velocity of the gas phase escalates from 0.5 m/s to 4 m/s, the average deposition rate experiences an increase of 82%. Similarly, when the apparent velocity of the liquid phase rises from 1 m/s to 5 m/s, the average deposition rate is amplified by a factor of 2.1. An increase in particle diameter from 50 μm to 400 μm results in a 27% increase in the average deposition rate. When the oil–gas interfacial tension is augmented from 0.02 n/m to 0.1 n/m, the average deposition rate witnesses an 18% increase. Furthermore, an increase in crude oil viscosity from 0.012 mPa·s to 0.06 mPa·s leads to a 34% increase in the average deposition rate. These research outcomes contribute to a deeper understanding of the asphaltene deposition problem under multiphase flow conditions and offer fresh perspectives on the asphaltene deposition issue in the oil and gas industry.